Determinants of life satisfaction among female-headed households in Malaysia - Moga Dass, Thinagaran (2018)
The general objective of this study was to determine the factors affecting life satisfaction among female-headed households in Malaysia. Five states in Malaysia were chosen through multi-stage sampling method. A total of 527 respondents were participated in this study. Descriptive analysis, independent sample t-test, One-way Analysis of Variance (Anova), and Multiple regression were used in the Statistical Package for Social Science version 22.0 (SPSS). The results show that the mean age for the respondents was 53.14 years old. Majority of the respondents were Malay followed by others, Indian and Chinese. The results show that 60.2% of them are having moderate level of financial capability, 57.8% of them in moderate level of financial vulnerability and 69.8% of them possess a moderate level of life satisfaction. Pearson correlation indicated that, personality (p= .000, b=.312), financial capability (p= .000, b=.159), and financial vulnerability (p= .000, b=.-224) has significant relationship with life satisfaction. Meanwhile, the independent sample t-test shows that higher income group has better life satisfaction compared to lower income group (t-value= -3.531, p= .000), non-savers has higher life satisfaction compared to people who frequently save (t-value= -4.277, p= .000) and female-headed households with assets more than debt has a higher life satisfaction (M=12.7660, SD=2.481). The multiple regressions show that, personality, financial capability and financial vulnerability are the significant predictors of life satisfaction among female-headed household in Malaysia.This study suggested that the findings are useful for the female-headed households, policy makers and non-governmental organizations. More attention should be given in building their self-confidence, and more control of themselves rather than being dependent on others on decision making. More knowledge and enhancement can be done on empowering the female-headed household on the modern financial instruments. By doing so, it can increase the financial capability and reduce the financial vulnerability of female-headed household in Malaysia towards a better life satisfaction.